PENGEMBANGAN MEDIA PEMBELAJARAN IPA SEKOLAH DASAR BERBASIS AUGMENTED REALITY SEBAGAI UPAYA MENGOPTIMALKAN HASIL BELAJAR SISWA - Ali Fakhrudin; Arief Kuswidyanarko (Jurnal Muara Pendidikan, 2020)
In this study, researchers developed augmented reality-based learning media for science subjects. This is research development. The results of the development have been validated by nine experts, including material experts, media experts, learning experts, linguists, and education practitioners. Based on the experts' validation, the media developed was declared valid with an Aiken value of 0.9528. Teacher and student assessments obtained 92.71 percent from the teacher and 88.07 from students. In conclusion, the media developed was categorized as very good and feasible to apply in learning. Besides, the trial testing results also showed that the developed media optimally improved students' learning outcomes in science subjects.